2014
DOI: 10.2337/db14-1279
|View full text |Cite
|
Sign up to set email alerts
|

Protein Ingestion Induces Muscle Insulin Resistance Independent of Leucine-Mediated mTOR Activation

Abstract: Increased plasma branched-chain amino acid concentrations are associated with insulin resistance, and intravenous amino acid infusion blunts insulin-mediated glucose disposal. We tested the hypothesis that protein ingestion impairs insulin-mediated glucose disposal by leucine-mediated mTOR signaling, which can inhibit AKT. We measured glucose disposal and muscle p-mTORSer2448, p-AKTSer473, and p-AKTThr308 in 22 women during a hyperinsulinemic-euglycemic clamp procedure with and without concomitant ingestion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 50 publications
2
70
1
Order By: Relevance
“…Data from studies conducted in cultured myotubes, isolated rat skeletal muscles and transgenic mice have demonstrated that amino acids, particularly the branched-chain amino acid leucine, can impair insulin-mediated glucose uptake by AMPK-mediated mTOR phosphorylation and subsequent negative feedback inhibition of PI3K-AKT signaling (Iwanaka et al, 2010, Saha et al, 2011) or possibly downstream signaling to 4E-BP1 (Tsai et al, 2015). In contrast, we recently found these pathways were not involved in the inhibition of insulin-mediated glucose uptake that occurred with acute protein ingestion in people (Smith et al, 2015). In the current study, we also found that chronic HP intake impaired the weight loss-induced improvement in insulin-mediated glucose uptake in the absence of differences in p-AMPK Thr172 , p-mTOR Ser2448 and p-4E-BP1 Thr37/46 in muscle.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Data from studies conducted in cultured myotubes, isolated rat skeletal muscles and transgenic mice have demonstrated that amino acids, particularly the branched-chain amino acid leucine, can impair insulin-mediated glucose uptake by AMPK-mediated mTOR phosphorylation and subsequent negative feedback inhibition of PI3K-AKT signaling (Iwanaka et al, 2010, Saha et al, 2011) or possibly downstream signaling to 4E-BP1 (Tsai et al, 2015). In contrast, we recently found these pathways were not involved in the inhibition of insulin-mediated glucose uptake that occurred with acute protein ingestion in people (Smith et al, 2015). In the current study, we also found that chronic HP intake impaired the weight loss-induced improvement in insulin-mediated glucose uptake in the absence of differences in p-AMPK Thr172 , p-mTOR Ser2448 and p-4E-BP1 Thr37/46 in muscle.…”
Section: Discussionmentioning
confidence: 80%
“…Total plasma free fatty acid concentration was quantified by using an enzymatic colorimetric assay (Wako Diagnostics, Richmond, VA). Plasma glucose and palmitate tracer-to-tracee ratios (TTR) were determined by using GC-MS as previously described (Smith et al, 2015, Mittendorfer et al, 2003b). C3- and C5-acylcarnitine concentrations in plasma were quantified by using liquid chromatography-tandem mass spectrometry (LC-MS/MS, Applied Biosystems Sciex 4000QTRAP with Eclipse C18 column) after adding known amounts of propionyl-L-carnitine ( N-trimethyl -d 3 ) and isovaleryl-L-carnitine ( N,N,N-trimethyl -d 9 ) (both purchased from Cambridge Isotope Laboratories Inc) as internal standards and their conversion to methylesters as described (with minor modifications) by Forni et al (2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic hyperaminoacidemia, induced by either intravenous amino acid infusion or protein ingestion, acutely reduces insulin-stimulated glucose disposal (13), and chronic high protein intake is associated with an increased risk of type 2 diabetes (47). The mechanism(s) responsible for the adverse effects of dietary protein intake and the concomitant increase in circulating amino acids on insulin sensitivity is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al (1) discussed the resistance to insulin properties of protein ingestion, focusing on the possible role of leucine as a master regulator of mTOR activation. But, finding leucine not guilty of insulin resistance is not a surprise as biochemistry indicates other amino acids as possible offenders.…”
mentioning
confidence: 99%